Embedded Memory Design for Multi-Core and Systems on Chip - Mohammad, Baker; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This book describes the various tradeoffs systems designers face when designing embedded memory.  Readers designing multi-core systems and systems on chip will benefit from the discussion of different topics from memory architecture, array organization, circuit design techniques and design for test.  The presentation enables a multi-disciplinary approach to chip design, which bridges the gap between the architecture level and circuit level, in order to address yield, reliability and power-related issues for embedded memory.  ·         Provides a comprehensive overview of embedded memory design and associated challenges and choices; ·         Explains tradeoffs and dependencies across different disciplines involved with multi-core and system on chip memory design; ·         Includes detailed discussion of memory hierarchy and its impact on energy and performance; ·         Uses real product examples to demonstrate embedded memory design flow from architecture, to circuit design, design for test and yield analysis.
Introduction -- Cache Architecture and Main Blocks -- Embedded Memory Hierarchy -- SRAM Memory Operation and Yield -- Low Power and High Yield SRAM Memory -- Leakage Reduction -- Embedded Memory Verification -- Embedded Memory Design Validation and Design For Test -- Emerging Memory Technology Opportunities and Challenges.
Keywords: Electronic circuits; Electronics; Microelectronics; Microprocessors; Circuits and Systems; Electronics and Microelectronics, Instrumentation; Processor Architectures